Comparative genomic analysis of mollicutes with and without a chaperonin system - Schwarz, Dominik; Adato, Orit; Horovitz, Amnon; Unger, Ron (PLOS ONE, 2018)
The GroE chaperonin system, which comprises GroEL and GroES, assists protein folding in vivo and in vitro. It is conserved in all prokaryotes except in most, but not all, members of the class of mollicutes. In Escherichia coli, about 60 proteins were found to be obligatory clients of the GroE system. Here, we describe the properties of the homologs of these GroE clients in mollicutes and the evolution of chaperonins in this class of bacteria. Comparing the properties of these homologs in mollicutes with and without chaperonins enabled us to search for features correlated with the presence of GroE. Interestingly, no sequence-based features of proteins such as average length, amino acid composition and predicted folding/disorder propensity were found to be affected by the absence of GroE. Other properties such as genome size and number of proteins were also found to not differ between mollicute species with and without GroE. Our data suggest that two clades of mollicutes re-acquired the GroE system, thereby supporting the view that gaining the system occurred polyphyletically and not monophyletically, as previously debated. Our data also suggest that there might have been three isolated cases of lateral gene transfer from specific bacterial sources. Taken together, our data indicate that loss of GroE does not involve crossing a high evolutionary barrier and can be compensated for by a small number of changes within the few dozen client proteins.